Editorial - Editor (Hamdard Islamicus, 2021)
The first issue of the Hamdard Islamicus for ongoing year, A.D. 2020, is composed of five research articles which will discuss the contemporary Western scholastic approaches regarding the Holy Qur’Én, Islamic stance regarding surrogacy, the approach of four Guided Caliphs of Islam and some financial issues discussed in the light of Islamic teachings. The first article namely “A Study of the Contemporary Western Academic Approaches to the History of the Qur’Én: The Case of the Encyclopaedia of the Qur’Én” deals with the approach followed by contemporary Western scholarship in determining the history of the Qur’Énic text .... a pivotal point of the Western studies regarding the Holy Qur’Én.